Risk of flare after tapering or withdrawal of biologic/targeted synthetic disease-modifying anti-rheumatic drugs in patients with rheumatoid arthritis or axial spondyloarthritis: a systematic review and meta-analysis. (3rd December 2021) - Uhrenholt, Line; Christensen, Robin; Dinesen, Wilfred K H; Liboriussen, Caroline H; Andersen, Stine S; Dreyer, Lene; Schlemmer, Annette; Hauge, Ellen-Margrethe; Skrubbeltrang, Conni; Taylor, Peter C; Kristensen, Salome
Abstract: Objective: To evaluate flare risk when tapering or withdrawing biologic or targeted synthetic DMARDs (bDMARDs or tsDMARDs) compared with continuation in patients with inflammatory arthritis in sustained remission or with low disease activity. Methods: Articles were identified in the Cochrane Library, PubMed, Embase and Web of Science. Eligible trials were randomized controlled trials comparing tapering and/or withdrawal of bDMARDs and/or tsDMARDs with the standard dose in inflammatory arthritis. Random effects meta-analysis was performed with risk ratio (RR) or Peto's odds ratio (POR) for sparse events and 95% CI. Results: The meta-analysis comprised 22 trials: 11 assessed tapering and 7 addressed withdrawal (4 assessed both). Only trials with an RA or axial SpA (axSpA) population were identified. An increased flare risk was demonstrated when b-/tsDMARD tapering was compared with continuation [RR 1.45 (95% CI 1.19, 1.77), I 2 = 42.5%] and potentially increased for persistent flare [POR 1.56 (95% CI 0.97, 2.52), I 2 = 0%]. Comparing TNF inhibitor (TNFi) withdrawal with continuation, a highly increased flare risk [RR 2.28 (95% CI 1.78, 2.93), I 2 = 78%] and increased odds of persistent flare [POR 3.41 (95% CI 1.91, 6.09), I 2 = 49%] were observed. No clear difference in flare risk between RA or axSpA was observed. Conclusion: A high risk for flare and persistent flare was demonstrated for TNFi withdrawal, whereas an increased risk for flare but not for persistent flare was observed for b-/tsDMARD tapering. Thus tapering seems to be the more favourable approach. Registration: PROSPERO (CRD42019136905).